TINDAK PIDANA PEMERASAN DAN PENGANCAMAN TERHADAP SESEORANG DENGAN MEDIA ELEKTRONIK YANG MENGANDUNG PORNOGRAFI (PUTUSAN NOMOR 331/PID.SUS/PN.JKT.SEL)or 331/Pid.Sus/PN.Jkt.Sel): Criminal Acts of Extortion and Threatening Someone with Electronic Media Containing Pornography (Decision Number 331/Pid.Sus/2022/PN.Jkt.Sel) - Taufik, Ahmad; Nuswanto, Heru Susetyo (AMICUS CURIAE, 2024)
The criminal act of extortion and threats with electronic media containing pornographyon social media was committed by the defendants Alfilah Ramadhan and IzzudinArrazzi. In this case the judge sentenced the defendant to Article 27 paragraph (4) inconjunction with Article 45 paragraph (4) of Law Number 19 of 2016 in conjunctionwith Article 55 paragraph (1) of the Criminal Code. Based on the discussion, thedefendant should have been subject to Article 27 paragraph (1) in conjunction withArticle 45 paragraph (1) of Law Number 19 of 2016 in conjunction with Article 55paragraph (1) of the Criminal Code. The issue that can be raised is whether the actionsof the perpetrators of the crime of extortion and threatening someone with electronicmedia containing pornography are appropriate based on Article 27 paragraph (4) inconjunction with Article 45 paragraph (4) of law number 19 of 2016 Jo Article 55paragraph (1 ) Criminal Code and whether the aggravating elements in the crime ofinformation and electronic transactions can be applied to cases of extortion and threatscontaining pornography in the decision. This type of research uses normative research,is descriptive analysis, secondary data, analyzed qualitatively, the method of drawingconclusions uses deductive logic. The writing of this law results in the actionscommitted by the two defendants fulfilling the elements of Article 27 paragraph (4) inconjunction with Article 45 paragraph (4) and Article 27 paragraph (1) in conjunctionwith Article 45 paragraph (1) of the ITE Law Jo Article 55 paragraph (1) of theCriminal Code and criminal sanctions using continuing and concurrent criminal acts.